KEDUDUKAN HUKUM (LEGAL STANDING) PEMOHON DALAM SENGKETA HASIL PEMILIHAN UMUM KEPALA DAERAH DI MAHKAMAH KONSTITUSI - Wahyuni, Ni Nyoman (Kertha Wicara : Journal Ilmu Hukum, 2015)
The paper is titled " The legal status ( legal standing ) Applicant In Dispute regional Election Results in the Constitutional Court ", used normative juridical and statute approach. Legal status ( legal standing ) is a requirement to submit a lawsuit to the Constitutional Court. These provisions determine who is entitled to be the applicant on the Election. In accordance with Article 326c Law 12 year 2008 the authority of the Constitutional Court be increased to handle the dispute directly Election results. The friction of authority give effect to the applicant 's legal position in a dispute over the results of the general elections of regional heads . Terms and conditions of the applicant and the application will be submitted now been determined directly into PMK No. 15 of 2008.
Keywords: Legal status, Applicant, Disputed Elections of Regional Heads, Constitutional Court